No nonsense pathology - Haque, Anwar Ul (International Journal of Pathology, 2023)
Some people find pathology very boring, dry, and difficult subject. For a person who desires to be a good doctor, it will certainly be very unfortunate to think so, as pathology solves the mysteries behind various diseases and deciphers the secrets behind various signs and symptoms. Pathology answers Why? What? When? Where and How? of symptoms and signs. No passionate doctor will find solving these puzzles boring or dry. In contrast he shall find it very absorbing, challenging, and helpful. Someone had rightly labeled pathologist as “Doctors’ Doctor” as he may answer the questions of other doctors due to his sound and deep knowledge of Pathology. A doctor should enjoy such a subject which does all that. It’s not only very challenging but also very satisfying and obliging. Perhaps for creating an impression of pathology as difficult and dry subject, there is role of some pathology books that give too much unnecessary details in a very boring style. In too many details one can’t find a needle in a haystack. The final Prophet of Allah Muhammad صلى الله عليه وسلمhas sought Allah’s protection from useless knowledge. Useless knowledge kills the very creativity. Allah, the Creator is the most Wise and Knowledgeable. He created everything with a purpose and in a superb organized logical manner